Human Resource Planning Study in Hot Strip Mill 2 (HSM#2) factory at PT. Krakatau Steel, Tbk - Dibyantoro; Abdul Chatim Pramono; Asep Rahmatullah; Ranthy Pancasasti (Program Studi S3 Ilmu Manajemen, 2021)
The purpose of this study was to analyze the human resource planning process at the Hot Strip Mill 2 (HSM#2) factory at PT. Krakatau Steel, Tbk from before it was established until the first commercial operation (first coil). The existence of human resource planning is very important forfactory new, so that human resources will be obtained in quantity and quality in accordance with the needs to support effectiveness and efficiency in order to achieve the vision and mission set by the company. HSM#2 factory isproduction work unitPT. Krakatau Steel, Tbk which started operating for the first time (first coil) on May 17, 2021. The research method is qualitative descriptive using a phenomenological approach that will reveal the experiences of leaders and the human resource planning department related to the HSM#2 factory. The number of informants is7 people consisting of2 persons the manager who makes the mapping of human resource needs, and5 staff person directly involved in human resource planning at the HSM#2 plant. Data were collected beforehand by using interview techniques, document studies, and field observations. Data were analyzed using SWOT matrix analysis by considering strengths, weaknesses, opportunities, and threats. The results of the study indicate that at the time of planning human resources, the procurement of employees is divided into two, namely those from internal for supervisory, superintendent, and manager positions and those frommix of internal and external for officer, foreman, and supervisor positions.